PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN FISCALL STRESS TERHADAP DERAJAT DESENTRALISASI FISKAL KABUPATEN/KOTA DI PROVINSI JAWA TENGAH 2007-2011 (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to examine the effect of local revenue (PAD), the General Allocation Fund (DAU), Special Allocation Fund (DAK) and Fiscall Stress on Fiscal Decentralization Degree of Regency / City in Central Java province in 2007-2011. The data used is Realized Budget Report regencies / cities sampled, published on its website www.djpk.depkeu.go.id. The sampling method used is the census because the object of this study is the all of 35 district and city in the province of Central Java. Types of data used are secondary data with panel data (pooled data) because it is a combination of time series and cross section data. The method of analysis used is the analysis of panel data with Pooling Least Square (PLS) and Generalized Least Square (GLS). The results showed that the variables local revenue have positive and significant impact on Fiscal Decentralization Degree, DAU have negative and significant impact on Fiscal Decentralization Degree, DAK have negative and significant impact on Fiscal Decentralization Degree, FiscallStress have positive and significant impact on Fiscal Decentralization Degree. Dependent Variable is Fiscal Decentralization Degre influenced by independent variables PAD, DAU, DAK and Fiscall Stress at 96.5% while the remaining 3.5% is explained by other variables outside the model. Keywords: Fiscal Decentralization Degree, Local Revenue (PAD), the General Allocation Fund (DAU), Special Allocation Fund (DAK), Fiscall Stress.